The Effectiveness of Adding Red Fruit Oil (Pandanus conoideus Lamk.) into Ethanol Extract of Temulawak rhizome (Curcuma xanthorrhiza Roxb.) as Antioxidant - Sari Purbaya; Lilis Siti Aisyah; Dona Nopitasari (Jurnal Kimia Sains dan Aplikasi, 2020)
Curcuma xanthorrhiza Roxb (temulawak) is a native Indonesian plant; ethnobotanically, it can facilitate breast milk, body fresheners, stomach lozenges, and seizure medications. Temulawak contains essential oils, curcuminoids, and xanthorrhizol. Curcuminoids and xanthorrhizol have potential as antioxidants. Antioxidants in the body are useful for preventing oxidation reactions caused by free radicals, both from body metabolism and external factors. Curcuminoids are difficult to dissolve in water and have a very low bioavailability. Combining curcuminoids with oil can increase the absorption of curcuminoids into the systemic system. The low solubility and bioavailability can be overcome by combining temulawak rhizome extract and red fruit oil. Pandanus conoideus Lamk (red fruit), ethnobotanically, effectively prevents blindness, intestinal worms, skin diseases, and increasing stamina. Red fruit contains vitamin C, vitamin E, flavonoids, and β-carotene, potentially as antioxidants. Each sample of Curcuma and red fruit, as well as a mixture of Curcuma and red fruit samples, were tested for their antioxidant activity using the DPPH method (1,1-diphenyl-2-picrylhydrazyl). The ethanol extract of temulawak rhizome has intense antioxidant activity because it has an IC50 of 55.21 ppm. Red fruit oil has feeble antioxidant activity because it has an IC50 of 2604.77 ppm. The 1: 1 ratio between red fruit oil and the ethanol extract of temulawak rhizome has weak antioxidant activity because it has an IC50 of only 1568.24 ppm. Meanwhile, the 1:10 ratio of red fruit oil and ethanol extract of temulawak rhizome has robust antioxidant activity because it has an IC50 of 19.85 ppm. It is concluded that the addition of oil to the ethanol extract of Curcuma can increase antioxidant activity.